Benefaction in Galatians - Wyman, David (Mohr Siebeck, 2025)
David Wyman examines documentary and literary sources to compose a detailed description of civic benefaction, including the phenomenon of benefactors who risk their lives. He then analyzes how Pauls letter to the Galatians incorporates the language, motifs, and relational dynamics of benefaction.
PublicationDate: 20250409
Keywords: Apostle Paul -- reciprocity -- self-endangerment -- Greek epigraphy -- Hellenistic society -- Sir Edward Craster -- Neues Testament -- Antike -- Alte Geschichte -- Antike Religionsgeschichte